In vitro assessment of pancreatic islet vitality by oxymetry - Zacharovová, Klára; Berková, Zuzana; Špaček, Tomáš; Kříž, Jan; Dovolilová, Eva; Girman, Peter; Koblas, Tomáš; Ježek, Petr; Saudek, František (Transplantation proceedings, 2005)
In order to assess the quality of freshly isolated and cultivated pancreatic islets designed for experimental transplantation in rats we combined the vitality staining test, in vitro measurement of insulin secretion capacity, and assessment of islet respiration. Oxygen consumption was measured using the respirometer Oxygraph 2K equipped with polarographic oxygen sensors. The results of oxymetry demonstrated a linear correlation between islet number and oxygen consumption. Respiration per unit of viable islet tissue was constant. Oxygen consumption tests were in good correlation with the results of insulin release assays, with a correlation coefficient of 0.82. We found no significant differences in all three vitality-testing methods performed with fresh and 24-hour cultivated islets (P > .05). We conclude that polarographic oxymetry provides a fast and easy evaluation test of islet quality. After appropriate standardization, the oxymetric technique can be used for routine clinical pretransplant islet quality testing. In addition, cell membrane integrity and mitochondrial function could be assessed after addition of specific respiration inhibitors or stimulators.
Keywords: inzulin; spotřeba kyslíku; Langerhansovy ostrůvky; Rats, Wistar; Rats; Animals; Oximetry; kultivované buňky; mužské pohlaví; potkani Wistar; viabilita buněk; oxymetrie; Cell Survival; zvířata; krysa rodu Rattus; Islets of Langerhans; Cells, Cultured; Insulin; Male; Oxygen Consumption